The implementation of the principles of the bologna process in english courses in bachelor's degree programmes in Turkey - Akbuz, Sevgül (My University, 2009)
Bu tezin amacı, Bologna Süreci esaslarının, Türk Yüksek Öğrenim Sistemi’ nde dört yıllık lisans öğrencilerine verilen İngilizce ders içeriklerine uygulanmasındaki etkileri incelemektir. Bu inceleme Yıldız Teknik ve Sakarya Üniversite’ lerde dört yıllık lisan eğitimi alınan öğrenciler için verilen zorunlu

ders içerikleri üzerine geliştirilmiştir. Bu çalışmada, Avrupa Birliği (AB) tarafından bir eğitim reform hareketi olarak başlatılan Bologna Süreci’ nin genişlemesini ve Türkiye’ nin 2001 yılında sürece dahil olmasını takip eden dönemde, zorunlu İngilizce derslerinin Bologna temel hedeflerini gerçekleştirmedeki rolü üzerinde durulmuştur. Bu bakımdan, tez Bologna Süreci temel hedefleri olan öğrenci ve akademik kadro hareketiliği ve mezunların iş bulabilirliği konusunda, İngilizce dil öğreniminin rolü konusuna odaklanmaktadır. Sürecin ana özelliklerinin yanısıra, ‘yeterlilikler’, ‘yeterlilikler çerçeveleri’, ve yeterliliklerleri oluşturan temel unsurlar gibi önemli kavramları içeren bir bölüm Bologna Süreci resmi dökümanlarıyla açıklanmakta ve irdelenmektedir. Tezin içerisinde yer alan kavramlar yukarıda adı geçen iki üniversiteden elde edilen verilerin değerlendirilmesinde yardımcı olmak için kullanılmaktadır. Bu çalışma, aynı zamanda, müfredat hazırlama aşamasında bahsedilen temel unsurlar ile zorunlu İngilizce dersleri arasındaki bağlantının önemini, bütün üniversitelerin lisans öğrencileri için İngilizce dil yeterliliklerini Türk Ulusal Yeterlilikler Çerçevesi ile birlikte tüm Avrupa Yüksek Öğrenim Alanında da tanımlanmış olması gerektiğini ortaya koymaktadır. Tezin en önemli bölümü, Bologna Süreci temel prensiplerinin lisans düzeyinde verilen İngilizce derslerinin müfredat incelemesi kısmından elde edilen sonuçların değerlendirilmesi için ayrılmıştır. Ulaşılan sonuçların ışığında, Türk Yüksek Öğretim Sistemindeki lisans öğrencileri için hazırlanan zorunlu İngilizce derslerinin müfredatlarında Bologna Süreci’ nden sonra görülen değişiklikler ya da yeni uygulamalar kapsamlı bir şekilde incelenmektedir. ABSTRACT This thesis aims at analysing the implementation of the Bologna Process principles on the content of English language courses for four-year Bachelor Degree students in the Turkish Higher Education. This analysis is built on the curricula of compulsory English courses offered in two Turkish Universities which are Yıldız Technical University and Sakarya University. Following the extension of the Bologna Process, started as an educational reform by the EU, and Turkey’s involvement in 2001, the contribution of compulsory English language courses for fulfilment of the major Bologna objectives has been emphasized in this present study. In this respect, this thesis focuses on the role of English language teaching/ learning in working towards the Bologna Process main objectives which are mobility of the students and academic staff and employability of the graduates. The background of the Bologna Process as well as its key features is explained and discussed through the official documents, including the reference points for some important concepts such as qualifications, qualifications frameworks, and the core key components of qualifications. The concepts presented in this thesis are aimed at helping the evaluation of the results obtained from the case studies taking place in two Turkish Universities mentioned above. This study then defines the relationship between these core elements and compulsory English courses while designing course curricula, suggesting that all universities should describe the English language qualifications for Bachelor Degree students throughout the European Higher Education Area as well as within the context of Turkish National Qualifications Framework. In particular, the important part of the thesis is then devoted to the evaluation of the results obtained from the curricula analysis part relevant to the implementation of the Bologna Process principles on English language teaching at Bachelor’s Degree. In the light of the findings, the changes and new implementations seen in the curricula of compulsory English courses offered for Bachelor Degree students in Turkish Higher Education after the Bologna Process have been comprehensively explored. TABLE OF CONTENTS Page No ÖZET............................................................................................................iii ABSTRACT.................................................................................................iv TABLE OF CONTENTS...........................................................................v THE LIST OF TABLES.............................................................................x THE LIST OF FIGURES...........................................................................xii THE LIST OF GRAPHS............................................................................xiii THE LIST OF ABBREVIATIONS...........................................................xiv INTRODUCTION.......................................................................................1 CHAPTER 1 I.THE BOLOGNA PROCESS VIS-À-VIS A LITERATURE REVIEW COUPLED WITH THE OBJECTIVES OF THE PROCESS AND AN OVERVIEW OF ENGLISH LANGUAGE TEACHING IN HIGHER EDUCATION IN EUROPE...................10 1.1Overview of the Bologna Process………………………………..10 1.1.1 Main Legal Documents of the Bologna Process…………..12 1.1.1.1Lisbon Recognition Convention…………………13 1.1.1.2Sorbonne Declaration…………………………….14 1.1.1.3Bologna Declaration………………………………15 1.1.1.4Lisbon Strategy…………………………………..15 1.1.1.5Prague Communiqué……………………………..16 1.1.1.6Graz Declaration………………………………….17 1.1.1.7Berlin Communiqué………………………………17 1.1.1.8Glasgow Declaration……………………………..18 1.1.1.9Bergen Communiqué……………………………..18 1.1.1.10Lisbon Declaration………………………………..19 1.1.1.11London Communiqué…………………………….20 1.1.1.12 Leuven/ Louvain – la - Neuve Communiqué……..21 1.1.2 Aims and Objectives of the Bologna Process…………......23 1.1.2.1Purposes and Action Lines of the Bologna Process..24 1.1.2.2The Relations between Languages and Mobility as an Objective of the Bologna Process……………...25 1.1.2.3The Relations between Languages and Employability as an Objective of the Bologna Process…………………………………………….27 1.2Teaching English in Higher Education in Europe………………29 1.2.1English Language Teaching in European Higher Education in Early Beginnings………………………….30 1.2.2Widespread Use of English in Europe in Relation to the Bologna Process…………………………………………30 CHAPTER 2 II.AN OVERALL ANALYSIS OF QUALIFICATIONS CONCEPT IN THE CONTEXT OF THE BOLOGNA PROCESS WITH SPECIFIC REFERENCE TO THE ENGLISH LANGUAGE QUALIFICATIONS IN HIGHER EDUCATION……………........34 2.1 Qualifications……………………………………………………35 2.1.1The Key Concepts of Qualifications………………………36 2.1.1.1 Levels of Higher Education……………………….37 2.1.1.2 Workload………………………………………….38 2.1.1.3 Quality…………………………………………….40 2.1.1.4 Profile……………………………………………..41 2.1.1.5 Learning Outcomes and Dublin Descriptors………43 2.1.2 Qualifications Frameworks……………………………….49 2.1.2.1 European Overarching Qualifications Frameworks.50 2.1.2.1.1 The Overarching Framework for the European Higher (QF – EHEA Framework)………………………………………..50 2.1.2.1.2 European Qualifications for Lifelong Learning Framework (EQF - LLL)………………..51 2.1.2.2 National Qualifications Frameworks in Europe…..55 2.1.2.2.1Countries Developing National Qualifications Frameworks……………56 2.1.2.2.1.1 The Irish National QF……..58 2.1.2.2.1.2The Scottish Credit and QF (SCQF)…………………….59 2.1.2.2.1.3 The Australian QF...............61 2.2 Language Qualifications in Higher Education in Europe with Reference to Language Qualifications Defined in Europe……...62 2.2.1 European Language Portfolio…………………………...66 2.2.2 The Implementation of ELPs in English Language Programmes in Three Participant Countries…………….69 CHAPTER 3 III.ANALYSIS OF THE IMPLEMENTATION OF BOLOGNA REFORMS ON ENGLISH LANGUAGE TEACHING IN TURKISH UNIVERSITIES WITH THE EVALUATION OF THE CURRICULA OF ENGLISH COURSES AVAILABLE IN YILDIZ TECHNICAL UNIVERSITY AND SAKARYA UNIVERSITY………………………………………………………...75 3.1 Overview of the Bologna Process Implementation in the Turkish Higher Education System………………………………………..75 3.1.1 Qualifications Frameworks and Recognition in the Bologna Process in Turkey……………………………...78 3.1.2The Preparation of Turkish National Qualifications Framework Regarding English Courses Offered in Turkish Universities……………………………………..80 3.2Teaching English as a Foreign Language; Language Policy in Turkish Higher Education……………………………………….81 3.3The Improvements and Changes in the Curricula of Compulsory English Courses with Regard to the Bologna Process in Two Distinguished Turkish Universities……………………………...83 3.3.1 General Description of Yıldız Technical University and Its English Language Teaching Policy…………………….....86 3.3.2 Curriculum Design Analysis of Compulsory English Courses Offered by the Modern Languages Department……………………………………………...88 3.3.2.1 9051031 (9101021) Advanced English I………….88 3.3.2.1.12005 – 2006 (Fall Semester) Course Training Programme Form………….......92 3.3.2.1.22006 – 2007/ 2007 – 2008/ 2008 – 2009 (fall Semester) Course Training Programme Form………………………..94 3.3.2.29051032 (9101022) Advanced English II………….95 3.3.2.2.12005 – 2006 (spring Semester) Course Training Programme Form……...............98 3.3.2.2.22006 – 2007/ 2008 – 2009 (spring semester) Course Training Programme Form……………………………………..99 3.3.2.2.3Departmental Outputs (Outcomes) for 9051032 Advanced English II Course…………………………………...99 3.3.2.2.4Annual Activity Reports for Academic Years (9051031 – 9051032)……………..101 3.3.2.2.52005 – 2006 Annual Activity Report for 9051031 – 9051032………….…………..101 3.3.2.2.62006 – 2007 Annual Activity Report for 9051031 – 9051032……………………..102 3.3.2.3 9052031 (9102021) Advanced English III/ Reading and Speaking in English.........................105 3.3.2.3.12004 – 2005/ 2005 – 2006/ 2006 – 2007/ 2008 – 2009 (fall semester) Course Training Programme Forms………….....................................107 3.3.2.3.2 Departmental Outputs (Outcomes) for the Advanced English III Reading and Speaking in English Course (9052031)…...........................................108 3.3.2.3.3Annual Activity Reports for Academic Years (9052031)……………….………109 3.3.2.3.42005 – 2006 Annual Activity Report for 9102021(Advanced English III), 9052031 (Reading and Speaking in English)………………………………..109 3.3.2.3.52006 – 2007 Annual Activity Report for 9102021(Advanced English III), 9052031 (Reading and Speaking in English)………………………………110 3.3.2.4 9053032 (9102021) Advanced English IV/ Business English………………………………..111 3.3.2.4.1Departmental Outputs (Outcomes) for the Advanced English IV – Business English Course (9053032)…………….114 3.3.2.4.2Annual Activity Reports for Academic Years (9053032)…….............................115 3.3.2.4.32005 – 2006 Annual Activity Report for 9102022 (Advanced English IV) 9053032 (Business English)…..............116 3.3.2.4.42006 – 2007 Annual Activity Report for 9102022 (Advanced English IV) 9053032 (Business English)…………..116 3.3.3 General Description of Sakarya University and Its English Language Teaching Policy………………………………...117 3.3.3.1 Curriculum Design Analysis of Compulsory English Courses Offered by the Department of Foreign Languages…............................................119 3.3.3.2English I/ English II……………………………..120 3.4 A Critical Evaluation of the Data Obtained from the Analyses of the Curricula of Compulsory English Courses in Relation to the Bologna Process……………………………………………..125 CONCLUSION………………………………………………………132 WORKS CITED……………………………………………………...147
Keywords: Avrupa Birliği; Bologna Süreci_Türkiye; Yabancı Dil; Yüksek Öğretim Kurumu (YÖK)